Svetozar Marković’s sociological and social contribution - Luknar, Ivana; Kalik, Mario (Sociološki pregled, 2026)
In this paper dedicated to the thematic section “Svetozar Marković: 150th death anniversary”, we strive to interpret and highlight Svetozar Marković’s sociological and social contribution to Serbian science on the basis of the qualitative content analysis, particularly in relation to the circumstances in Serbia and the Balkans. Marković’s reflections still represent the enlightening guidelines for intellectuals dealing with social matters, advocating for the protection of national interests and encouraging the development of local and regional communities. They are guided by the idea of society that serves real needs of working people in an attempt to overcome contradictions deriving from capital accumulation. Quite expectedly, many Marković’s attitudes seem obsolete and idealistic, having in mind that almost a century and a half have passed since their creation. Nevertheless, many of his interpretations may still encourage modern thought and offer an insight into social and political issues encountered by the Serbian nation in today’s socio-historical context.
Keywords: Svetozar Marković (1846–1875); centralism; local self-government; socialism; Serbian literature